Thermal stability of Cu/W nano-multilayers. (1st April 2016) - Moszner, F.; Cancellieri, C.; Chiodi, M.; Yoon, S.; Ariosa, D.; Janczak-Rusch, J.; Jeurgens, L.P.H.
Abstract: The thermal stability of Cu/W nano-multilayers in the temperature range of 400 °C– 800 °C has been investigated by high-resolution scanning electron microcopy, X-ray photoelectron spectroscopy and X-ray diffraction. A repetition of 100 alternating nanolayers of Cu and W with individual thicknesses of 5 nm were prepared by magnetron sputter deposition on an α-Al2 O3 substrate. In the as-deposited state, the nano-multilayers exhibit pronounced Cu <111> and W <110> textures with a Cu{111}<10 1 ¯ >||W{110}<00 1 ¯ > orientation relationship. Annealing at T  ≥ 500 °C results in the appearance of a high number of line-shaped protrusions on the outer surface, which are composed of facetted Cu particles. Annealing at T  ≥ 700 °C leads to a gradual degradation of the initial layered structure towards a spheroidized nanocomposite consisting of globular W particles embedded in a Cu matrix (after annealing at 800 °C). An average activation energy of 257 ± 21 kJ/mol (2.66 ± 0.22 eV) related to this degradation process is determined by in-situ high-temperature X-ray diffraction. The experimentally obtained activation energy indicates that the morphological transformation is governed by the diffusion of W along internal interfaces such as Cu/W interphase boundaries and W/W grain boundaries. Graphical abstract: